Jahresbericht 2021 der Universitätsbibliotheken der TU Berlin und UdK Berlin - Christof, Jürgen; Zeyns, Andrea (Wissen im Zentrum : Rechenschaftsbericht / Universitätsbibliothek, Technische Universität Berlin, 2022)
In their seventh joint Annual Report, the University Libraries of Technische Universität Berlin (TU Berlin) and Universität der Künste Berlin (UdK Berlin) look back on the year 2021, a year that brought new offers and services despite difficult conditions, including the coronavirus pandemic. These include the extension of the opening hours until midnight and the introduction of the Leganto tool for the easy creation of literature lists. Staff report on team management models, changing organizational structures, and the long-planned and now finally completed move of the preprint series of the Institute of Mathematics at TU Berlin. In addition, the TU University Archives, Architekturmuseum as well as the Media Library of the UdK present their special holdings and offers. An illustrated calendar lists important events from 2021. The 2021 Annual Report is concluded with an overview of selected key figures, information about the subject librarians, and a list of publications by library staff.